Construction and implementation of a 4-probe measuring system to determinate the temperature dependent sheet resistance of thin films - Pacheco Arenas, Carlos Arturo (2016)
In order to build machines, electronic devices, it is necessary to know all properties of the materials. The machines and electronic devices use parts that are interconnected, the mechanical properties are important, but for some specific tasks the electrical properties are more important. In this sense it is necessary to predict the behavior of this parts in different temperatures to the environment. The present thesis focus on implementation of a 4-probe measuring system to determinate the sheet resistance of thin film samples showing the dependency of the resistivity on the film thickness as well as on the deposition temperature. The method used to determine the resistivity is the modified van der Pauw Method. Therefore, it is important the measurement of the current and the voltage drop in the sample. It is also important to measure the distance between tips, in order to calculate the resistivity. Furthermore, it is also important to find the correct transformation that maps any four point of a plane to a new plane with four collinear points. The measurements are controlled via LabVIEW and the measured data is displayed in the user interface.